Effects of Cyclosporine on Reperfusion Injury in Patients: A Meta-Analysis of Randomized Controlled Trials. (16th June 2015) - Song, Kangxing; Wang, Shuxia; Qi, Dake
Abstract : Mitochondrial permeability transition pore (mPTP) opening due to its role in regulating ROS generation contributes to cardiac reperfusion injury. In animals, cyclosporine (cyclosporine A, CsA), an inhibitor of mPTP, has been found to prevent reperfusion injury following acute myocardial infarction. However, the effects of CsA in reperfusion injury in clinical patients are not elucidated. We performed a meta-analysis using published clinical studies and electronic databases. Relevant data were extracted using standardized algorithms and additional data were obtained directly from investigators as indicated. Five randomized controlled blind trials were included in our meta-analysis. The clinical outcomes including infarct size (SMD: −0.41; 95% CI: −0.81, 0.01;P = 0.058), left ventricular ejection fraction (LVEF) (SMD: 0.20; 95% CI: −0.02, 0.42;P = 0.079), troponin I (TnI) (SMD: −0.21; 95% CI: −0.49, 0.07;P = 0.149), creatine kinase (CK) (SMD: −0.32; 95% CI: −0.98, 0.35;P = 0.352), and creatine kinase-MB isoenzyme (CK-MB) (SMD: −0.06; 95% CI: −0.35, 0.23;P = 0.689) suggested that there is no significant difference on cardiac function and injury with or without CsA treatment. Our results indicated that, unlike the positive effects of CsA in animal models, CsA administration may not protect heart from reperfusion injury in clinical patients with myocardial infarction.